Biomarkers in heart failure: the importance of inconvenient details. (25th November 2015) - Miller, Wayne L.; Jaffe, Allan S.
Abstract: The proliferation of cardiac‐related biomarkers and advocacy for their use has often come without adequate discussion of limitations in the interpretation of values and their best use in heart failure (HF) patients to provide a balanced assessment of how cardiac biomarkers are advocated for use in HF and areas where we would argue there are no gaps in knowledge. We include suggestions to address these issues. We have focused on peer‐reviewed publications over the period 2000 to present. Most studies have used samples at one or at most two points in time to define risk. Although biomarkers might add to the magnitude of risk, it is unclear how often they lead to changes in treatment. We suggest that defining the use of serial biomarker testing over time would be more helpful. To do this, it is necessary to take into account the biomarker's analytical and biological variability in addition to its ability to define and monitor therapy. These factors are often overlooked leading to conclusions that may be statistically significant but not clinically or analytically robust. An appreciation of the value and limitations of biomarker use is important to all clinicians who manage HF patients. If the proper studies are done so that biomarkers are used optimally, they will likely be helpful in defining when and how to intervene. If we continue as we have, we will continue to have ambiguity about the use of these valuable probes in the assessment and management of HF.